Synthesis, Crystal Structure and Hirshfeld Surface Analysis of (E)-2 - Acar, E.; Kansiz, S.; Dege, N. (Pleiades Publishing Ltd, 2023)
(E)-2-(4-methylbenzylidene)-N-phenylhydrazine-1-carbothioamide was synthesized by reacting chalcone with phenylthiosemicarbazide in ethanolic sodium hydroxide. The resulting compound, C H-15 N-15 S-3, was characterized using various spectroscopic techniques, including single-crystal X-ray diffraction, IR, 1H NMR, and C-13 NMR spectroscopy. The molecule has an E configuration around the central C=N double bond and crystallizes in the triclinic system, with space group P-1. The asymmetric unit contains two independent molecules of phenylthiosemicarbazide and phenylhydrazine, both of which are non-planar. The crystal structure is stabilized by C-H.S and N-H.S hydrogen bonds, which connect the molecules to form a three-dimensional network. The availability of efficient donors and acceptors for hydrogen bonding results in a well-connected three-dimensional structure. Furthermore, Hirshfeld surface analysis was conducted to examine the potential hydrogen bonding and the location of atoms in the compound. This analysis revealed the numerical ratio of hydrogen bonding and the atoms with potential to form these Furthermore, Hirshfeld surface analysis was conducted to examine the potential hydrogen bonding and the location of atoms in the compound. This analysis revealed the numerical ratio of hydrogen bonding and the atoms with potential to form these contacts.
Keywords: Schiff Base; Phenylthiosemicarbazide; Phenylhydrazine; Crystal Structure; Hirshfeld Surface